Functional traits explain the consistent resistance of biodiversity to plant invasion under nitrogen enrichment. (31st December 2021) - Li, Shao‐peng; Jia, Pu; Fan, Shu‐ya; Wu, Yingtong; Liu, Xiang; Meng, Yani; Li, Yue; Shu, Wen‐sheng; Li, Jin‐tian; Jiang, Lin
Abstract: Elton's biotic resistance hypothesis, which posits that diverse communities should be more resistant to biological invasions, has received considerable experimental support. However, it remains unclear whether such a negative diversity–invasibility relationship would persist under anthropogenic environmental change. By using the common ragweed ( Ambrosia artemisiifolia ) as a model invader, our 4‐year grassland experiment demonstrated consistently negative relationships between resident species diversity and community invasibility, irrespective of nitrogen addition, a result further supported by a meta‐analysis. Importantly, our experiment showed that plant diversity consistently resisted invasion simultaneously through increased resident biomass, increased trait dissimilarity among residents, and increased community‐weighted means of resource‐conservative traits that strongly resist invasion, pointing to the importance of both trait complementarity and sampling effects for invasion resistance even under resource enrichment. Our study provides unique evidence that considering species' functional traits can help further our understanding of biotic resistance to biological invasions in a changing environment. Abstract : Whether biodiversity would consistently resist invasion under global change scenarios is poorly understood. Our four‐year grassland experiment showed that plant diversity was a consistent barrier to common ragweed invasion irrespective of nitrogen addition, and that plant diversity resisted invasion simultaneously through increases in the biomass, functional diversity, and dominance of conservative traits, of the resident communities.